2021
DOI: 10.1155/2021/9994303
|View full text |Cite|
|
Sign up to set email alerts
|

The Current Situation and Influencing Factors of the Alarm Fatigue of Nurses’ Medical Equipment in the Intensive Care Unit Based on Intelligent Medical Care

Abstract: After rapid development and reform, the health level and medical diagnosis and treatment capabilities of Chinese residents have been significantly improved, and high-quality medical resources have significantly improved the life safety and health of the masses. As the most concentrated area of medical equipment in the hospital, the intensive care unit produces the most alarms during the operation of the equipment. The intensive care unit nurses are responsible for heavier nursing work, and the problem of alarm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…Also Bourji et al (2020) show that the mean alarm fatigue score was higher in males and in nurses with higher levels of education [ 38 ]. But Zhao et al (2021) show that high education are negatively correlated with alarm fatigue [ 39 ]. Perhaps the reason for this difference is in the existence of COVID-19 condition and the type and environment of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Also Bourji et al (2020) show that the mean alarm fatigue score was higher in males and in nurses with higher levels of education [ 38 ]. But Zhao et al (2021) show that high education are negatively correlated with alarm fatigue [ 39 ]. Perhaps the reason for this difference is in the existence of COVID-19 condition and the type and environment of the study.…”
Section: Discussionmentioning
confidence: 99%
“…It was determined that the ICU nurses who participated in this study had moderate alarm fatigue levels (Table 2). Among previous studies, levels of alarm fatigue among intensive care nurses were reported to be high in China 24 and to be moderate 5 in Korea. In their study conducted in Pennsylvania in the United States, Storm and Chen 23 found the alarm fatigue rate of intensive care nurses as 40%, while Elhessewi and Eldin 25 in the Behira Governorate in Egypt determined this rate to be 66.92%.…”
Section: Discussionmentioning
confidence: 91%
“…25 Another study result also shows that high-level positions, long working years, high professional titles, and high education are negatively correlated with alarm fatigue. 26 Notwithstanding the interesting results, this research has some limitations. The first limitation of this study was that the perceptions of all critical care nurses were not included as they also adopting alarm monitoring in the nursing performance.…”
Section: Part Ii: Relationship Between Nurses' Alarm Fatigue and Vari...mentioning
confidence: 88%